Phytophthora ramorum and Phytophthora kernoviae on naturally infected asymptomatic foliage - Denman, S; Kirk, S A; Moralejo, E; Webber, J F (EPPO Bulletin, 2009)
Phytophthora ramorum and Phytophthora kernoviae are recently discovered invasive Phytophthoras causing leaf necrosis and shoot tip dieback mostly on ornamental and forest understorey species, but also cause bleeding cankers on stems of a wide range of tree species. Sporulation occurs only on infected shoots or fruits and foliage so foliar hosts are central to the disease epidemiology. In field trials to assess infection in trap plants exposed to natural inoculum of P. ramorum and P. kernoviae on rhododendron in south west England, it was discovered that leaves of the trap plants (Rhododendron‘Cunninghams White’) and holm oak (Quercus ilex) were asymptomatically infected and supported sporulation of both pathogens. More than half the rhododendron trap plants exposed to inoculum of P. kernoviae became infected compared with approximately a third of those exposed to P. ramorum in a natural situation. Approximately one third of the infections were detected from asymptomatic foliage for both pathogens. The significance of these findings for plant health regulation based on visual inspection as a measure to prevent introduction and dissemination of both these pathogens is explored and research gaps identified.
Keywords: asymptomatic infection; pathogen sporulation (voyant); Phytophthora kernoviae; Phytophthora ramorum

Phytophthora kernoviae and P. ramorum: host susceptibility and sporulation potential on foliage of susceptible trees1 - Denman, S; Kirk, S; Whybrow, A; Orton, E; Webber, J F (EPPO Bulletin, 2006)
Phytophthora kernoviae and P. ramorum are introduced, invasive pathogens in the UK. Both species are adapted for aerial dispersion and have a wide host range, many of which are common to both pathogens. The diseases they cause are foliar necrosis and shoot tip dieback on both tree and ornamental hosts, and bleeding cankers on tree hosts. Inoculum is produced on infected foliage but not on bleeding cankers in both cases. Proactive measures to prevent disease spread and to evaluate the risks posed by these pathogens are being undertaken. Amongst others, these include using the detached leaf assay to get an indication of tree foliage susceptibility, and inoculating wounded stems of saplings to get an idea of under-canopy sapling and nursery tree susceptibility. The sporulation potential on selected susceptible hosts was assessed, and finally, surveys which are still ongoing were carried out in south-west England. Results of this work are presented and discussed.
Keywords: host tree; Phytophthora kernoviae; Phytophthora ramorum; resistance; sporulation potential (voyant); susceptibility